(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The study undertaken during the year 2021 –2022 (July to April), deals with thorough chemical investigation of soil samples collected from different study sites around cement industry in varying seasons, located in Raebareli District. Samples estimated in a regular interval of 3 months (July, Oct, Jan & April) for seasonal variations. The dust emitted from the Cement Company, located in Raebareli, gets deposited in course of time over the soil, leaves and forms a grey cover on the surrounding soils. The concentration of micro nutrient Fe, Cr, Zn, Cu is very high in most of the sampling sites. Extremely high concentration of Fe (60 to 200 ppm) and Cr (72 to 99 ppm) reported almost in all seasons. pH showed highly alkaline (8.2 to 11.3) nature of soil.